Leadership Decision-Making and Insights in Higher Education: Making Better Decisions and Making Decisions Better - Stephanie Chitpin (Ali Khorsandi Taskoh, 2021)
This article proposes a new framework for Principals called the Objective Knowledge Growth Framework (OKGF) that is designed to help them make more effective decisions in resolving problems of practice. It also provides a structure to help principals break away from education systems that impose inductive practices, as it provides a framework for supporting the decision-making processes of others as well as enabling rationality in their own practice. The use of the OKGF framework is designed to enhance individual reflection which, in turn, is multiplied by others through dialogue, interaction and engagement with others. Through interaction, dialogue and engagement, greater and improved insights into decisions are more likely to occur than if knowledge and information continues to be compartmentalized within schools and, consequently, performance assessments are more likely to be enhanced. Not only does the OKGF have the capacity to improve principals' performance, it also provides a framework by which principals may maximize student success.